Farsighted rationality in hedonic games - Ghislain-Herman Demeze-Jouatsa; Dominik Karos (Bielefeld University, Center for Mathematical Economics (IMW), 2021)
We consider a hedonic coalition formation game in which at each possible partition any new coalition can decide the probability with which to form and leave the current partition. These probabilities are commonly known so that farsighted players can decide whether or not to support a coalition's move: they know which future partition, and hence payoffs, will be reached with what probability. We show that if coalitions make mistakes with positive probability, i.e., if they choose probabilities that are always above some e > 0, then there is a behavior profile in which no coalition has a profitable one-shot deviation.
urn:nbn:de:0070-pub-29579246
Keywords: C71; C72; 519; abstract games; hedonic games; farsighted stability; coalition stable equilibrium